Leśmian’s poetry Russian and English translations) in the realm of intertextuality - Katarzyna Lukas (Przestrzenie Teorii, 2014)
Marta Kaźmierczak’s book which is titled Przekład w kręgu intertekstualności. Na materiale tłumaczeń poezji Bolesława Leśmiana [“Translation and intertextuality: a study based on the translations of Bolesław Leśmian’s poetry”] is the first comprehensive monograph on Bolesław Leśmian’s poems that have been translated into English and Russian. The aim of the study is to examine how the “intertextual signals” from the source texts were translated into languages that are cognate with and distantly related to Polish. The author understands intertextuality as a significant relationship between a particular literary text and another text, a group of texts (e.g. philosophical), or cultural texts (e.g. a macrotext concerning Slavonic beliefs) that come before a given text in time. The intertextual elements in Leśmian’s poems are classified thematically, i.e. according to the domain to which they refer and based on the extent to which they are recognizable to those who have read the texts that are referred to.